CATCALLING SEBAGAI BENTUK PELECEHAN SEKSUAL PADA PEREMPUAN SERTA UPAYA PENGENTASANNYA - Nur Hasanah; Muhammad Alridho Lubis; Siti Nahdhiatus Soleha; Dwi Maryani; Setiani Nurhayati; Deby Manalu; Silvia Maharani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Catcalling is a form of harassment that involves teasing, teasing, calling, or verbally commenting on someone, usually a woman. This can include various forms of teasing, including insulting words, seeking attention, or trying to cause discomfort. Catcalling often occurs in public places and can cause stress, discomfort, and even physical threats for the victim. Sexual harassment is an unexpected and unwanted act, but we cannot cover up the prevalence of sexual harassment in society, starting from verbal and non-verbal actions. This research is a qualitative study that uses literature review methods and literature journal reviews. The data collection process is carried out by reviewing and analyzing articles that have been published and can be accessed through platforms such as Google Scholar and Publish or Perish. The aim of this approach is to gain an in-depth understanding of the catcalling phenomenon and efforts to eradicate it as well as to identify the forms and the cause of the catcalling. The results of this research show that catcalling is a complex problem that requires a multidimensional approach in alleviating it. This research also highlights the importance of public education and awareness about sexual harassment and women's rights to be part of efforts to eradicate it. Apart from that, guidance and counseling can also provide support to victims through counseling services designed to help them in the recovery process after experiencing sexual harassment.